The Thermal Image of Sun Orientation and Openings in Residential Buildings with Modern Tropical Design Concept in Medan City - harry wibowo; sembiring, Dicky Andrea (Jurnal Koridor, 2023)
This study aims to analyze thermal imagery of the sun's orientation and the formation of openings in residential houses with a modern tropical design concept in Medan. The method used is temperature measurement and building thermal identification using a digital thermal imaging tool, namely Flir CX-3, which is carried out during the day, as well as measuring the WWR (window-to-wall ratio) value of the building. The results of the thermal image analysis show that the North-South orientation gets lower temperatures compared to the East-West orientation, even though it has a larger WWR value of 12.9% and 20.9%. Based on the results of this analysis, it is suggested to consider the orientation of the sun in designing residential houses in the city of Medan. Houses with a North-South orientation are the best choice for maximum thermal comfort and natural lighting, supported by large openings as one of the characteristics of modern tropical architecture.